a) There are a+(n-1)d logs in the nth layer, with 'a' referring to the first number in the sequence (5) and 'd' referring to the common difference (1). n refers to the layer which you are looking at.

5+(n-1)1 = 5+n-1 = n+4

to prove > we know the third layer will have 7 logs in. 3+4 = 7

b) Here you must use the equation for finding the sum of the terms in an arithmetic sequence.

a=5

d=1

n=?

Sn=?

Sn=1/2n [2a + (n-1)d]

Sn=1/2n [10 + (n-1)1]

Sn=1/2n [10 + n - 1]

Sn=1/2n [n + 9]

There she blows